Assessment of aerosol radiation environment in short-range region of ChNPP during building of the new safe confinement - Garger, E.K.; Shynkarenko, V.K.; Kashpur, V.A.; Skorjak, G.G.; Kalinovsky, A.K. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2017)
Variability of ¹³⁷Cs volume activity in a subsurface layer of the atmosphere of a short-range region of the object "Shelter" (object "Ukryttya") during the works on building of a new safety confinement in 2016 was investigated. Influence of the type and location of works, weather conditions, and sampling points was shown. Excess of medial permissible concentrations of ¹³⁷Cs in the air was not fixed during the observations. However, due to the averaging of the measured values of the volume activity for the exposure time of the filter and use of the stationary aerosol samplers, it cannot ensure the absence of excess of the permissible concentrations at the locations of works and on the propagation path of the local emission plumes. In 2016, as well as in 2013 - 2015, high levels of ¹³⁷Cs volume activity in the air were preferentially localized near to the machine hall of the 4th block and near to the places of ground works at the industrial site [ 1]. Concurrently the levels of volume activity essentially grew (practically by the order of magnitude) due to the intense works on the machine hall transformation. The conservative estimation of volume activity of isotopes of the plutonium, executed in the assumption of fuel composition of hot particles, showed the presence of substantial excess of permissible limits even for the average values within, at least, four weeks. Absence of reliable correlation (R = -0.09) of ¹³⁷Cs volume activity in the air near to the machine hall and near to the aerosol sampler 1,4 km remote from it testifies the localization of pollution within the industrial site.